Pengembangan Media Pembelajaran Sosiologi Berbasis Animaker pada Materi Konflik Sosial Kelas XI di SMAN 3 Kota Cilegon - Alifa, Asyika Nur; Kuntari, Septi; Hardiansyah, Muhammad Agus (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This research aims to determine the feasibility and practicality of animaker-based sociology learning media on social conflict material for class. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. In this model, it only reaches the evaluation stage which is obtained from suggestions or comments from validators and students to be used as a reference for the product to be used. The results of the data analysis described above consist of 3 discussions, namely (1) media expert trial results, (2) material expert trial results, and (3) student trial results. The results obtained from the media expert validation data analysis were a total of 72 out of a maximum total of 85. Based on these calculations, the average product validation obtained by media experts was 84%, so it can be seen that this animaker-based sociology learning media product is found among 81<100% very decent. Analysis of material expert validation data, namely a total of 44 out of a maximum total of 65. Based on these calculations, the average product validation by material experts is 67%, so it can be seen that this animaker-based sociology learning media product is found between 61-80%. (worthy). The results of the total student assessment obtained were 74%, it can be seen that the Animaker-based sociology learning media product was between 61<80% (feasible).